Academician's perceptions of the liaison librarian service at Universiti Putra Malaysia Library: a case study - Hamzah, Norhazura; Ab. Rahman, Azwana (Persatuan Pustakwan Malaysia, 2014)
The Liaison librarian service is a means to provide the connection between all academician at the various faculties and institutes and the university library. This service was introduced at Universiti Putra Malaysia Library in the 1980's but had not been assessed. The main task of a liaison librarian is to develop a relationship with faculty members, to convey information about the library, research, publications, etc, which will help towards a well-planned library collection development as well as being a facilitator in the information literacy program. The objective of this study is to identify the awareness and use of this service among academicians, to identify the important service that should be provided by a liaison librarian, to examine the regularity of faculty requests for assisstance from the liaison librarian and to analyze the preffered medium communication between the liaison librarians and academicians. A set of online questionnaire was distributed in July 2013 and the 78 respondents who participated are lecturers and tutors. This case study found that majority of the respondent are aware of the existence of the liaison librarian at UPM library. The need for representation at faculty function and activities was not considered as an important services to them. Impact of liaison services in research, teaching and student work was highly positive. Communication between faculty members and liaison occur periodically and they prefer to use email as the medium of communication.